2015
DOI: 10.1111/jfb.12756
|View full text |Cite
|
Sign up to set email alerts
|

Geographical variability in life‐history traits of a midslope dogfish: the brier shark Deania calcea

Abstract: Deania calcea (n = 420) were collected from the catch of deep-water trawlers in the southern and eastern scalefish and shark fishery in southern Australia during the years 2008-2011. The total length (LT ) range varied between sexes, females being larger (n = 264; 280-1530 mm) than males (n = 156; 310-921 mm). The reproductive cycle in this population is non-continuous and asynchronous. The estimated LT at which 50% of males are mature is 807 mm and is 914 mm for females. Populations of D. calcea in higher lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The variation in all these studies could be due to latitude or plasticity of the reproductive cycle of this species, and could be potentially related to environmental conditions. More regional studies on spiny dogfish and elasmobranchs in general are required to determine whether differences observed are truly specific to a region or are due to plasticity or size (or both), or age of the female (Lombardi- Carlson et al, 2003;Driggers and Hoffmayer, 2009;Hoffmayer et al, 2013;Rochowski et al, 2015;Taylor et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The variation in all these studies could be due to latitude or plasticity of the reproductive cycle of this species, and could be potentially related to environmental conditions. More regional studies on spiny dogfish and elasmobranchs in general are required to determine whether differences observed are truly specific to a region or are due to plasticity or size (or both), or age of the female (Lombardi- Carlson et al, 2003;Driggers and Hoffmayer, 2009;Hoffmayer et al, 2013;Rochowski et al, 2015;Taylor et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…McCulloch 1915 Daley et al (2002), but four of the 2711 specimens reported by Moura et al (2014) were longer (1260, 1360, 1420 and 1620 mm; all females) and among 420 specimens examined by Rochowski et al (2015), the largest female was 1530 mm 376 Deania hystricosa (Garman 1906 Bigelow & Schroeder (1948). Maximum sizes of 315 mm precaudal length (Longley & Hildebrand, 1941) and 500 mm L T (Compagno, 1984a) probably refer to the subsequently described and very similar E. robinsi, which attains a greater maximum size according to Schofield & Burgess (1997).…”
Section: Centrophorus Harrissonimentioning
confidence: 94%
“…In addition to interspecific variability, intraspecific and geographic variation in life-history traits is also widespread and has been reported in coastal and deep-water sharks (Parsons, 1993;Lombardi-Carlson et al, 2003;Motta et al, 2007;Farrell et al, 2010;Rochowski et al, 2015). In some cases, larger length at maturity and maximum size have been linked with higher latitude and, correspondingly, lower water temperature (Yamaguchi et al, 2000;Lombardi-Carlson et al, 2003), which might be explained by the ecological principle known as James' Rule (an intraspecific version of Bergman's Rule) (Blackburn et al, 2008).…”
Section: Introductionmentioning
confidence: 99%